Synthesis and in vitro Anti Microbial Evaluation Including Anti-Malarial Activity of Pyrazole Based Novel Cinnoline Derivatives - S. Hurmath Unnissa, Nilofer Nisha, Gayam Krishna Reddy (Journal of Applied Pharmaceutical Science, 2015)
A Series of 4-methyl-3-[5-(substituted phenyl)-4, 5-dihydro-1H-Pyrazol-3-yl] Cinnoline-6-Sulfonamide were synthesized from 4-methyl-3-acetylcinnoline-6-Sulfonamido chalcones and hydrazines. The structure of the synthesized compounds were characterized by UV, IR, NMR & Mass spectral data, and evaluated for their in vitro anti-malarial and anti-bacterial activity to get new congeners as analogs of Pyrazole based Cinnoline compounds as a potent anti-Malarial and anti-microbial agents. All analogues exhibited in vitro anti-malarial activity against Plasmodium falciparum and all the analogues showed good anti-bacterial activity against various pathogenic microbes.
Keywords: Cinnoline, pyrazole, Plasmodium falciparum, anti-bacterial, chalcones.